Are the evolutionary implications of vertical transmission of knowledge conservative? - Soldati, Gustavo Taboada; Albuquerque, Ulysses Paulino (Ethnobiology and Conservation, 2016)
The evolution of cultural systems, or the rate of change in the frequency of traits, is determined by the routes of knowledge transmission, among other factors. According to mathematical models, vertical transmission is the more conservative route, and it promotes high variation among individuals of a population, acts as a barrier to the diffusion of innovations, and promotes slow cultural evolution. However, the history of transmission of the same cultural traits beyond "model-apprentice" pairs indicates that vertical transmission can produce different effects on a cultural system. In the present paper we formalize the hypothesis that vertical transmission has diffusive effects and results in a fast change cultural evolution. If the hypothesis proposed here is confirmed, the theoretical reformulation and relativization of empirical data collected in previous studies will be required.